Public Spending, Enrolment, and Economic Growth: A Study of Higher Education in Nepal - Dahal, Gehendra Prasad; Khanal, Basudeb; Adhikari, Damodar; Ghimire, Maheshwor; Luitel, Giri Raj; Dhakal, Sudarshan (Nepal Journal of Multidisciplinary Research, 2025)
Background: Higher education is a key component of human-capital formation and is widely viewed as a driver of long-run economic growth. In Nepal, however, empirical evidence on the macroeconomic contribution of higher education remains limited, particularly over an extended period marked by political transition, federal restructuring, and changing development priorities. This study examines whether public investment and enrolment expansion in higher education have translated into sustained economic growth, while accounting for persistent concerns related to skill mismatch and institutional effectiveness. Methods: The study utilised annual time-series data for the period 1990-2024. Government expenditure on higher education (as a share of total education budget) and tertiary enrolment rates were employed as proxies for advanced human-capital investment. The Autoregressive Distributed Lag (ARDL) bounds-testing approach was applied to examine long-run relationships and short-run dynamics between higher education variables and real GDP growth. Standard diagnostic and stability tests were conducted to ensure model validity. Results: The findings revealed a positive and statistically significant long-run relationship between higher education expenditure and economic growth. Tertiary enrolment also exhibited a positive association with growth, although its impact appeared conditional on institutional quality and labour-market alignment. Short-run effects were presented but comparatively weaker, reflecting the gradual nature of human capital accumulation. Conclusion: The results indicate that enrolment expansion alone is insufficient to maximise higher education’s growth contribution. Policy effectiveness depends on quality-enhancing investment, institutional efficiency, and improved alignment between graduate skills and economic demand. Novelty: This study provides one of the longest ARDL-based analyses of higher education and economic growth in Nepal, integrating both expenditure and enrolment within a single dynamic framework and offering policy-relevant insights beyond access-focused approaches.